The use of head-mounted display eyeglasses for teaching surgical skills: A prospective randomised study. (October 2016) - Peden, Robert G.; Mercer, Rachel; Tatham, Andrew J.
Abstract: Purpose: To investigate whether 'surgeon's eye view' videos provided via head-mounted displays can improve skill acquisition and satisfaction in basic surgical training compared with conventional wet-lab teaching. Methods: A prospective randomised study of 14 medical students with no prior suturing experience, randomised to 3 groups: 1) conventional teaching; 2) head-mounted display-assisted teaching and 3) head-mounted display self-learning. All were instructed in interrupted suturing followed by 15 minutes' practice. Head-mounted displays provided a 'surgeon's eye view' video demonstrating the technique, available during practice. Subsequently students undertook a practical assessment, where suturing was videoed and graded by masked assessors using a 10-point surgical skill score (1 = very poor technique, 10 = very good technique). Students completed a questionnaire assessing confidence and satisfaction. Results: Suturing ability after teaching was similar between groups (P = 0.229, Kruskal-Wallis test). Median surgical skill scores were 7.5 (range 6–10), 6 (range 3–8) and 7 (range 1–7) following head-mounted display-assisted teaching, conventional teaching, and head-mounted display self-learning respectively. There was good agreement between graders regarding surgical skill scores (rho.c = 0.599, r = 0.603), and no difference in number of sutures placed between groups (P = 0.120). The head-mounted display-assisted teaching group reported greater enjoyment than those attending conventional teaching (P = 0.033). Head-mounted display self-learning was regarded as least useful (7.4 vs 9.0 for conventional teaching, P = 0.021), but more enjoyable than conventional teaching (9.6 vs 8.0, P = 0.050). Conclusions: Teaching augmented with head-mounted displays was significantly more enjoyable than conventional teaching. Students undertaking self-directed learning using head-mounted displays with pre-recorded videos had comparable skill acquisition to those attending traditional wet-lab tutorials. Highlights: Head-mounted displays have been used in a variety of roles in medicine and surgical education. Head-mounted displays did not improve surgical ability acquisition. Head-mounted display teaching was more enjoyable than conventional teaching. Head-mounted display self-learning gave equivalent skill acquisition to conventional teaching.